Current biopsy practices for suspected melanoma: A survey of family physicians in Southwestern Ontario. Issue 3 (August 2014) - Lutz, Kristina; Hayward, Victoria; Joseph, Mariamma; Wong, Eric; Temple-Oberle, Claire
Background: Family physicians (FPs) have an opportunity to diagnose pigmented lesions early with a timely biopsy. Objective: To assess current biopsy practices used by FPs in diagnosing melanoma. Methods: A computer-generated random sample of 200 practicing FPs from large and small communities in Southwestern Ontario was identified from the College of Physicians and Surgeons of Ontario physician directory. Paper-based surveys exploring practice setting, basic melanoma knowledge, biopsy practices and referral wait times were mailed using a modified Dillman protocol. Results: The response rate was 50% and respondents reflected the demographic characteristics of FPs nationwide as per the National Physician Survey. Knowledge testing revealed reasonable mean (± SD) scores (3.2±1.03 of 5). Twenty percent of respondents would always perform an excisional biopsy of skin lesions suspicious for melanoma. The remaining 80% would avoid an excisional biopsy in an aesthetically sensitive area and if there was risk of failure to close the defect primarily, among other reasons. If an excisional biopsy were not performed, one-half of respondents would perform an incisional biopsy (eg, punch biopsy). In large communities, 24% of patients were not seen by a surgeon within six months when referred without a tissue biopsy, leading to delayed diagnosis. Discussion: Educating and supporting FPs to perform incisional biopsies in cases for which excisional biopsies are inappropriate should result in earlier diagnosis of melanoma. Conclusion: FPs appropriately recognize that excisional biopsies are ideal in melanoma management and one-half will move on to an incisional biopsy when excision is not appropriate.